Determinan keunggulan bersaing - Clarisa Alfa Lionora; Amie Kusumawardhani (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Padang, 2021)
An increase in the number of business units in the apparel industry that occurs in the city of Semarang can be a problem, because the increase in business units in the apparel industry is directly proportional to the high level of competition in the industry. This study aims to analyze what factors can make a business unit in the apparel industry with a micro and small scale, especially in the city of Semarang, can excel in the competition. In the city of Semarang, there are 138 business units for the apparel industry with micro and small scale that will be investigated. Of all these business units, only 127 research data can be processed for this research. This study shows that there is a positive influence on the relationship between market orientation and learning orientation variables on product innovation variables and market orientation, learning orientation, and product innovation variables on competitive advantage variables. While there is no effect on the relationship between the variables of relational capital to competitive advantage. This research can be implemented by academics and practitioners in developing strategies to gain competitive advantage in the apparel industry in Semarang City.Keywords: Market orientation; learning orientation; relational capital; product innovation; competitive advantageTRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian // TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//